Corporate Accountability in Law Enforcement: Challenges in Proving and Punishing Corporate Crimes (Indonesian Court and Justice Review, 2024)
Corporate crime poses a growing threat to economic integrity, public safety, and environmental sustainability, yet legal systems often struggle to hold corporations accountable. This study explores the challenges faced by Indonesian law enforcement agencies and courts in proving and prosecuting corporate crimes, ranging from environmental violations to corruption and financial fraud. Through analysis of selected case studies, court judgments, and interviews with prosecutors, investigators, and legal scholars, the research identifies key barriers such as evidentiary complexity, corporate shielding structures, weak regulatory frameworks, and institutional reluctance. The study highlights the limitations of current legal tools in attributing liability to corporate entities, especially in the absence of clear standards for corporate intent and culpability. It also discusses recent legal reforms and their potential to improve enforcement. The novelty of this study lies in its comprehensive examination of both procedural and structural barriers to corporate accountability. It offers policy recommendations for strengthening corporate criminal liability mechanisms and ensuring that justice is not evaded through legal and institutional loopholes.